Peran Spiritual Dalam Penyembuhan Skizofrenia : A Literature Review - Fadma Aji Pramudita; Iman Permana (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Mental health is one of the health problems in the world, including in Indonesia, one of which is schizophrenia. Management of schizophrenia not only uses pharmacological therapy but also with non-pharmacological therapy. Spirituality is believed to have a role in the treatment of schizophrenia. Purpose: This article aims to identify and analyze research articles about the spiritual role in healing in schizophrenic patients. This article search uses a literature study approach from several ProQuest, Ebsco ScienceDirect databases, and Google Scholar databases, using the keywords